2015
DOI: 10.21608/zumj.2015.4518
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stromal Blood Flow After Laparoscopic Ovarian Drilling in Women With Polycystic Ovary Syndrome

Abstract: Background: Women with polycystic ovary syndrome have significant difference in their ovarian stromal blood flow indices when compared to women with normal ovaries. The intra-ovarian blood flow is assessed by studying small arteries in the ovarian stroma not close to the surface of the ovary or near the wall of the follicles. Aim: To assess the value of changes in Doppler indices of ovarian stromal blood flow and hormonal profile in women with PCOS and previously described as being clomiphene citrate resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Majority of patients were overweight [BMI in all groups was around 27 kg/m 2 ]. Ismail et al [20] reported that, patient age, body mass index [BMI], infertility duration, pattern of menstrual cycle and type of infertility did not differ significantly between study groups. Additionally, Lebbi et al [21] reported that 77% of them were presented with high BMI with a mean value of 27.8 kg/m².…”
Section: Discussionmentioning
confidence: 99%
“…Majority of patients were overweight [BMI in all groups was around 27 kg/m 2 ]. Ismail et al [20] reported that, patient age, body mass index [BMI], infertility duration, pattern of menstrual cycle and type of infertility did not differ significantly between study groups. Additionally, Lebbi et al [21] reported that 77% of them were presented with high BMI with a mean value of 27.8 kg/m².…”
Section: Discussionmentioning
confidence: 99%